2002
DOI: 10.1590/s0041-87812002000400003
|View full text |Cite
|
Sign up to set email alerts
|

Acute pleuropulmonary complications detected by computed tomography following myocardial revascularization

Abstract: INTRODUCTION:Pleuropulmonary changes are common following coronary artery bypass grafting surgery performed with a saphenous vein graft, with or without an internal mammary artery. The presence of atelectasis or pleural effusions reflects the thoracic trauma.PURPOSE: To define the postoperative incidence of changes in the lung and in the pleural space and to evaluate the influence of the trauma.METHODS: Thirty patients underwent elective coronary artery bypass grafting surgery (8 saphenous vein grafts and 22 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 18 publications
2
15
1
3
Order By: Relevance
“…Regarding the effect of IMA harvesting technique, bilateral IMA harvesting or pleural opening on respiratory function are controversial. Some authors noted an increased incidence of pulmonary complications in patients with open pleural IMA harvesting technique 5‐18 . We have also seen extremely high incidence of left pleural effusion on day 3 (96.2%) in patients with open pleural group.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Regarding the effect of IMA harvesting technique, bilateral IMA harvesting or pleural opening on respiratory function are controversial. Some authors noted an increased incidence of pulmonary complications in patients with open pleural IMA harvesting technique 5‐18 . We have also seen extremely high incidence of left pleural effusion on day 3 (96.2%) in patients with open pleural group.…”
Section: Discussionsupporting
confidence: 58%
“…Some authors noted an increased incidence of pulmonary complications in patients with open pleural IMA harvesting technique. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] We have also seen extremely high incidence of left pleural effusion on day 3 (96.2%) in patients with open pleural group. Incidence of left pleural effusion was significantly low in patients with preserved pleural integrity, both on day 1 and day 3 (37.6% and 60.8%, respectively).…”
Section: Discussionmentioning
confidence: 91%
“…It was found at a rate of 32% and 43.9% on the 2 nd and 3 rd postoperative day (POD), respectively [20]. Westerdahl et al [21] found it in 63% of patients on the 4 th POD, data similar to the study of Vargas et al [38], on which the authors used TCT as preliminary tool.…”
Section: Resultsmentioning
confidence: 54%
“…Vargas et al [24] studied by computed tomography (CT) the presence of atelectasis and pleural effusion in the postoperative period of CABG and found that all patients on the 2nd POD presented some degree of atelectasis or pleural effusion. However, they also state that the vast majority of the pleural effusions observed by CT were minimal and the atelectasis were laminar, or that is, most of these findings can not be observed on radiographs.…”
Section: Time In Icu and Total Hospital Stay Timementioning
confidence: 99%